PENGARUH PROMOTION, ONLINE CUSTOMER REVIEW DAN PRICE CONSCIOUSNESS TERHADAP PURCHASE INTENTION PADA PENGGUNA SHOPEE DI SOLO RAYA - Syaskia Moethya Aulia Az’zahra; Budi Istiyanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the influence of promotion, online customer reviews, and price consciousness on repurchase intention among Shopee users in Solo Raya. The independent variables used in this research are Promotion (X1), Online Customer Review (X2), and Price Consciousness (X3) and Purchase Intention as the dependent variable. The data in this research is primary data taken using a questionnaire distributed via Google Form to social media via direct message. The population of this research is consumers who have shopped using Shopee in Solo Raya. Sampling was carried out using Non-Probability Sampling with purposive sampling technique. The total sample was 90 respondents. The data analysis technique used is multiple linear regression analysis with partial results or t test showing that the Promotion (X1) and Online Customer Review (X2) variables have a calculated t value > t table 1.98793 and a significance value smaller than 0.05. so that the variables promotion and online customer reviews have a significant positive influence on purchase intention among Shopee users in Solo Raya. Meanwhile, the variable Price Consciousness (X3) has t count < t table -1.98793 and a significance value greater than 0.05, so the price consciousness variable is among Shopee users in Solo Raya.